A complex thermal history of the Southern Highlands preserved in Martian meteorite NWA7533 and its pairs - Bellucci, J.; Nemchin, Alexander; Whitehouse, M. (John Wiley & Sons, Inc., 2014)
This study presents new U-Pb chronology on zircons and phosphates in martian regolith breccia NWA 7533 and implications for its magmatic and subsequent thermal history.